Granger causality between stock market and selected macroeconomic indicators: Evidence from the Philippines - Bardullas, Kenneth Richard O. (Animo Repository, 2023)
This study utilizes the Toda-Yamamoto (1995) method to evaluate the Granger causality between the Stock Market index and a few macroeconomic indices. The Philippine Stock Exchange index (PSEi), which represents the stock market, is the subject of this study, which focuses on monthly data from January 2007 to December 2021. Macroeconomic indicators include Consumer Price Index, Exchange Rate, Industrial Production, Interest Rate, Money Supply, and Trade Balance. First, results has shown that the Consumer Price Index and Money Supply are both granger caused by the PSEi. Second, the Stock Market has shown a negative relationship with Exchange Rate, Industrial production, and Trade Balance. Third, Interest Rate has no significant relationship with the PSEi. Lastly, macroeconomic indicators didn’t indicate significant results to be conclusive, thus their relationship with the stock market cannot be concluded. Indicating that the PSEi is informationally efficient in regards to the selected macroeconomic indicators in the study.